Medical care information support for patients with drug-resistant tuberculosis in the Kemerovo Region - S. V. Saranchina; I. F. Kopylova; O. V. Ivanova; L. A. Lomova (Бюллетень сибирской медицины, 2012)
Introduced for the purpose of increase of rendering of quality of medical care in to service of the Kemerovo region the computer program «Monitoring of TB patients with drug-resistance» in a complex with other programs provides control over selection on treatment, completeness and frequency rate of inspection, adequacy and efficiency of treatment TB patients with drug-resistance, work of the specialized medical commissions.